2018
DOI: 10.4269/ajtmh.17-0416
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Tetravalent Dengue DNA Vaccine Administered with a Cationic Lipid-Based Adjuvant in a Phase 1 Clinical Trial

Abstract: Abstract.We conducted an open label, dose escalation Phase 1 clinical trial of a tetravalent dengue DNA vaccine (TVDV) formulated in Vaxfectin® to assess safety and immunogenicity. A total of 40 dengue- and flavivirus-naive volunteers received either low-dose (1 mg) TVDV alone (N = 10, group 1), low-dose TVDV (1 mg) formulated in Vaxfectin (N = 10, group 2), or high-dose TVDV (2 mg, group 3) formulated in Vaxfectin® (N = 20). Subjects were immunized intramuscularly with three doses on a 0-, 30-, 90-day schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 23 publications
0
52
0
Order By: Relevance
“…Mixed sera of dengue patients can react to many non-speci c DENV epitopes. The DENV tetravalent DNA vaccine is well tolerated and capable of generating a su cient anti-dengue interferon-gamma-mediated T-cell response (Danko et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mixed sera of dengue patients can react to many non-speci c DENV epitopes. The DENV tetravalent DNA vaccine is well tolerated and capable of generating a su cient anti-dengue interferon-gamma-mediated T-cell response (Danko et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of tetravalent DNA vaccine (TVDV), tetravalent purified formalin-inactivated virus (TPIV), and tetra-live attenuated virus (TLAV)-enhanced vaccination strategy was tested in rhesus monkeys, and monkeys immunized with TVDV/TVDV/TLAV were partially protected while TPIV/TLAV immunized monkeys were completely free of viremia [64]. In phase 1 clinical trials, a TVDV with Vaxfectin ® (Vical, Boulder, CO, USA) adjuvant was found to trigger anti-dengue T cell IFNγ response with ideal safety [100].…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…Data from a phase I trial of TVDV, which was completed in 2013, have just been reported recently. It was found that TVDV elicited predominantly anti-DENV T-cell interferongamma responses in a dose-dependent manner (Danko et al, 2018).…”
Section: Dengue Vaccine Candidates Currently In Clinical Trialsmentioning
confidence: 99%